Culture shapes efficiency of facial age judgments. - Gizelle Anzures; Liezhong Ge; Zhe Wang; Shoji Itakura; Kang Lee (PLoS ONE, 2010)
Cultural differences in socialization can lead to characteristic differences in how we perceive the world. Consistent with this influence of differential experience, our perception of faces (e.g., preference, recognition ability) is shaped by our previous experience with different groups of individuals.Here, we examined whether cultural differences in social practices influence our perception of faces. Japanese, Chinese, and Asian-Canadian young adults made relative age judgments (i.e., which of these two faces is older?) for East Asian faces. Cross-cultural differences in the emphasis on respect for older individuals was reflected in participants' latency in facial age judgments for middle-age adult faces--with the Japanese young adults performing the fastest, followed by the Chinese, then the Asian-Canadians. In addition, consistent with the differential behavioural and linguistic markers used in the Japanese culture when interacting with individuals younger than oneself, only the Japanese young adults showed an advantage in judging the relative age of children's faces.Our results show that different sociocultural practices shape our efficiency in processing facial age information. The impact of culture may potentially calibrate other aspects of face processing.